Inheritance of glyphosate resistance trait and its yield expressions in three-way cross maize hybrids - Magulama, Efren E. (USM R & D Journal, 2009)
The study aimed to determine the inheritance of glyphosate resistance trait in maize and evaluate the yield performance of three-way cross hybrids when incorporated with glyphosate resistance gene, and to assess the response of the same hybrids to glyphosate application. Inheritance study revealed that among the six phenotypic ratios tested, the glyphosate resistance trait followed in a 3:1 Mendelian ratio. This observation was noted in both types of population tested (F2 derived random mating population and S1 population) with respective chi-square values of 0.30 and 0.07 having P-values of 0.58 and 0.79. This suggests that the glyphosate resistance trait is controlled by single dominant gene. Among the 14 three-way cross hybrids evaluated, five hybrids outyielded the two check hybrids. These five hybrids had yields ranging from 6.30 to 8.66t/ha with an average yield advantage of 17% over the mean yield of the two check hybrids. It was further noted that reciprocal crosses(6.54t/ha) had greater yield than the F1 crosses (5.72 t/ha), which occurred when the roundup ready (RR) F1 hybrid was used as pollinator. Interestingly, a higher percentage of plant survival against glyphosate application was obtained from reciprocal crosses than the F1 crosses. About 40% plant survival percentage (SP) was noted in reciprocal crosses and only 4% SP in F1 crosses. The result need further investigation to elucidate why there was lesser SP of plant F1 crosses than in reciprocal crosses.